Energy Conservation Guidebook - Patrick, Dale R.; Fardo, Stephen W.; Richardson, Ray E.; Fardo, Brian W. (Routledge, 2023)
Revised and edited, this new third edition reference covers the full scope of energy management techniques and applications for new and existing buildings, with emphasis on the "systems" approach to developing an effective overall energy management strategy. Foremost in the enhancements to the new edition is content that reflects the emphasis on conservation for "green energy" awareness. Also examined are building structural considerations, such as heat loss and gain, windows, and insulation. A thorough discussion of heating and cooling systems basics is provided, along with energy management guidelines. Also covered are energy conservation measures that may be applied for lighting systems, water systems, and electrical systems. Specific energy management technologies and their application are discussed in detail, including solar energy systems, energy management systems, and alternative energy technologies.